Heart to heart with Asian leaders : exclusive interviews on crisis, comebacks & character - Ng, John, 1954-; Ng, John Swee Kheng, 1954-; Foo, Alvin Jong Peng (Singapore : World Scientific Publishing, 2015)
'An in-depth look at leadership issues first-hand with 29 prominent leaders in the Asia Pacific region'--
Keywords: Businesspeople -- Asia -- Interviews; Businesspeople -- Pacific Area -- Interviews; Civic leaders -- Asia -- Interviews; Civic leaders -- Pacific Area -- Interviews; Leadership -- Asia; Leadership -- Pacific Area